Use of ultraviolet-fluorescence-based simulation in evaluation of personal protective equipment worn for first assessment and care of a patient with suspected high-consequence infectious disease - Hall, S.; Poller, B.; Bailey, C.; Gregory, S.; Clark, R.; Roberts, P.; Tunbridge, A.; Poran, V.; Evans, C.; Crook, B. (The Journal of hospital infection, 2018)
Variations currently exist across the UK in the choice of personal protective equipment (PPE) used by healthcare workers when caring for patients with suspected high-consequence infectious diseases (HCIDs). To test the protection afforded to healthcare workers by current PPE ensembles during assessment of a suspected HCID case, and to provide an evidence base to justify proposal of a unified PPE ensemble for healthcare workers across the UK. One ‘basic level’ (enhanced precautions) PPE ensemble and five ‘suspected case’ PPE ensembles were evaluated in volunteer trials using ‘Violet’; an ultraviolet-fluorescence-based simulation exercise to visualize exposure/contamination events. Contamination was photographed and mapped. There were 147 post-simulation and 31 post-doffing contamination events, from a maximum of 980, when evaluating the basic level of PPE. Therefore, this PPE ensemble did not afford adequate protection, primarily due to direct contamination of exposed areas of the skin. For the five suspected case ensembles, 1584 post-simulation contamination events were recorded, from a maximum of 5110. Twelve post-doffing contamination events were also observed (face, two events; neck, one event; forearm, one event; lower legs, eight events). All suspected case PPE ensembles either had post-doffing contamination events or other significant disadvantages to their use. This identified the need to design a unified PPE ensemble and doffing procedure, incorporating the most protective PPE considered for each body area. This work has been presented to, and reviewed by, key stakeholders to decide on a proposed unified ensemble, subject to further evaluation.